2014
DOI: 10.1208/s12248-014-9689-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Imprecision in Incurred Sample Reanalysis for Small Molecules

Abstract: Abstract. Over the years, incurred sample (IS) reanalysis (ISR) has become a tool to confirm the reliability of bioanalytical measurements. The recommendation for ISR acceptance criterion for small molecules is at least 67% of ISR samples that have reanalyzed concentrations within 20% of their original concentrations when normalized to their means. To understand the relevance of the ISR acceptance criterion and sample size requirements, simulated ISR studies evaluated the probability of ISR studies passing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Unlike the regulated bioanalysis requirement for assessing ISR after completion of every study when the drug enters drug development (Fluhler et al, ; Hoffman, ; Subramaniam, Patel, Davit, & Conner, ; Timmerman et al, ), we wanted to check the feasibility of a system that examines ISR on a periodic basis (i.e. half‐yearly) without over‐burdening the throughput analysis and rapid data turnaround time, which are mandatory at the drug discovery stage.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike the regulated bioanalysis requirement for assessing ISR after completion of every study when the drug enters drug development (Fluhler et al, ; Hoffman, ; Subramaniam, Patel, Davit, & Conner, ; Timmerman et al, ), we wanted to check the feasibility of a system that examines ISR on a periodic basis (i.e. half‐yearly) without over‐burdening the throughput analysis and rapid data turnaround time, which are mandatory at the drug discovery stage.…”
Section: Methodsmentioning
confidence: 99%
“…The calculations using the hypergeometric distribution are complementary to the published simulations (10,18,19), but they have significant advantages. The novel model uses %ISR to include both random (imprecision) and systematic (bias, metabolite conversion) errors.…”
Section: Discussionmentioning
confidence: 99%
“…The Global Bioanalysis Consortium suggested, in turn, to reanalyze the fixed ratio of 5% of clinical samples that is equal to the ratio of quality control (QC) samples in a bioanalytical batch (9). More recently, Subraminiam et al presented a comprehensive ISR simulation for small molecules using various combinations of precision and bias (10). It revealed that if 20 ISRs are analyzed and the method’s precision up to 15% is combined with the bias not exceeding 10%, then over 0.85 of the studies pass the ISR test.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incurred sample reanalysis (ISR) was performed as a supplement to verify the reproducibility of the bioanalytical method . The ISR was conducted by remeasurement of subsamples; the acceptance criteria was that the difference between initial and reanalyzed concentrations when normalized to their means should be within 20.0% for at least two thirds of the samples.…”
Section: Methodsmentioning
confidence: 99%